Study of Relationship between Organizational commitment of Nurses with Managment Styles of Head Nurses in Teraputic Wards of outpatients veterans on 2010 - M. Ghiasi; A. Hekmatpor; E. Ehsani; M. Mahbobi; A. Afkar (Afarand Scholarly Publishing Institute, 2011)
Introduction : Todays, management science and different styles of it are the most factors in increase of personals productivity in health sectors for provide of approprate services specialy for veterans. Therefore the purpose of this Study was surrvey of Relationship between Organizational commitments of Nurses with Managment Styles of Head Nurses in Teraputic Wards of outpatients veterans on 2010.   Materials & Methodes : This is a discriptive study that Data was collected by two standard riminding staff and leadership styles questionnaires and data collected was analysis by statistics discriptive techniques. Results: Findings showed that total score of organizational commitment was 2.4240. also in four management styles, scores of authoritative style,charitable style, participatory style and consultative style were 116, 0.206, 738 and 0.998.   Conclusion : That, despite the positive correlation between Participative style of head nurses significent related with organizational commitment of nurses in under study centers then this can be approprate way that lead to increase of nurses productivity for provide of approprate services for veterans of war in teraputic and special sectores of hospital in around the country...